Come on up to the house [compact disc] : women sing Waits. - Waits, Tom, 1949- (Dualtone Music Group, 2019)
Compiled in honor of Tom Waits's 70th birthday, this is a unique amalgamation of fresh interpretations of songs by the legendary songwriter. Aimee Mann, Joseph, Patty Griffin, Rosanne Cash, Phoebe Bridgers, Corinne Bailey Rae, Angie McMahon, Courtney Marie Andrews, and more put their own unique spin on the gravel-voiced troubadour's work.